Modification of gasification slag-based functional soil for oat grass cultivation - Liu, Tengteng; Han, Fenglan; Yang, Baoguo; Xing, Zhibing; Wang, Jiaqi; An, Changcong; Dong, Xiongwei (Frontiers in Environmental Science, 2022)
Gasification furnace slag is a substrate that can be used effectively in plant ecological restoration projects. Using this substrate can contribute to sustainable development in the ecological environment construction. This study used a gasification furnace slag sample as the matrix material of functional soil based on an evaporation experiment of functional soil and a pot experiment of oat grass. Therefore, fly ash, YJF (organic nutrient regulator), and SJJXWS (water retaining agent) amendments were applied to study the physical, chemical, and agronomic characteristics of the functional soil, such as the seedling emergence rate and plant weight. The results showed that the water evaporation capacity, pH, conductivity, bulk density, available phosphorus, available potassium, organic matter, and other relevant agronomic properties of the functional soil changed according to the amendment type used. Also, it was found that the functional soil amended with YJF and SJJXWS could promote plant growth compared to the control. The results of this study can provide a theoretical basis for further development of functional soil for ecological cycle restoration purposes.